2021
DOI: 10.3389/fonc.2021.789078
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Trial of an Autologous Dendritic Cell Vaccine Against HER2 Shows Safety and Preliminary Clinical Efficacy

Abstract: BackgroundDespite recent advances, there is an urgent need for agents targeting HER2-expressing cancers other than breast cancer. We report a phase I study (NCT01730118) of a dendritic cell (DC) vaccine targeting HER2 in patients with metastatic cancer or bladder cancer at high risk of relapse.Patients and MethodsPart 1 of the study enrolled patients with HER2-expressing metastatic cancer that had progressed after at least standard treatment and patients who underwent definitive treatment for invasive bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…One patient achieved a complete response (CR), one achieved a partial response (PR), and five patients achieved disease stabilization (DS). Significantly, the study showed no AE with transduced DC therapy [109]. In the study NCT01826877, DCs delivering antigens via an adenoviral vector were also tested.…”
Section: Progenitor-based Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…One patient achieved a complete response (CR), one achieved a partial response (PR), and five patients achieved disease stabilization (DS). Significantly, the study showed no AE with transduced DC therapy [109]. In the study NCT01826877, DCs delivering antigens via an adenoviral vector were also tested.…”
Section: Progenitor-based Therapymentioning
confidence: 99%
“…To date, a multitude of clinical trials have used different DC vaccines, with the majority of them utilizing monocyte-derived DCs for loading with antigens [60,62,108,109], while only a few highlight the use of neoantigens [61]. Some studies employ DCs of natural myeloid origin [110]; however, the method of generating DCs from monocytes is considered the most commonly encountered.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The DC vaccine platform allows for antigen processing by the patient's own immune system, eliciting immunological responses against multiple epitopes on the target, versus a single epitope approach with an antibody or a small-molecule inhibitor. Preliminary studies using DC vaccines have been conducted in patients with invasive BC and even DCIS; the latter hinting at the potential for possible development of a vaccine for prevention of BC [196][197][198][199] . Although DC vaccines are a promising individualized strategy, the vaccine manufacturing process is complex and will need to be streamlined to make it more accessible.…”
Section: Cancer Vaccines Targeting Her2mentioning
confidence: 99%
“…To improve the DCV procedure, an antiFoxP3+ Treg depletion immunotoxin was administered before giving viral modified DCV, improving immunogenicity in advanced BC patients [ 54 ]. Another group treated metastatic HER2-positive bladder and BC patients with DCs transduced with an adenoviral vector expressing different HER2 domains, demonstrating clinical benefits in up to one third of the patients, together with immune responses [ 55 ].…”
Section: DC Vaccines In Solid Tumorsmentioning
confidence: 99%
“…In a non-randomized clinical trial for early disease, Qi et al treated non-luminal BC patients with tumor lysate-pulsed DCV, showing benefits in 3-year PFS, although they found no impact on OS, with almost 60% of the patients showing immune delayed hypersensitivity responses [ 55 ]. Lowenfeld et al vaccinated ductal carcinoma in situ (DCIS) and early HER2-positive BC patients before breast surgery with HER2 peptide-pulsed DCV and showed 28% of pathological complete response (pCR) in DCIS (only 8.5% in BC), with immunogenic activity in the sentinel lymph nodes as well as in the systemic blood, with no adverse effects [ 56 ].…”
Section: DC Vaccines In Solid Tumorsmentioning
confidence: 99%